2021
DOI: 10.1055/a-1352-5023
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Care During COVID-19 Pandemic in Singapore Using a Telehealth Strategy

Abstract: Singapore currently has one of highest number of confirmed COVID-19 cases in Southeast Asia. To curb the further spread of COVID-19, Singapore government announced a temporary nationwide lockdown (circuit breaker). In view of restrictions of patients’ mobility and the enforcement of safe distancing measures, usual in-person visits were discouraged. Here we describe how diabetes care delivery was ad hoc redesigned applying a telehealth strategy. We describe a retrospective assessment of subjects with diabetes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 3 publications
0
19
0
Order By: Relevance
“…We suggest that healthcare systems should take actions to mitigate this shortcoming by allocating resources to primary care and geriatric clinics in order increase screening and diagnosis of new dementia cases. Decrease in registered dementia cases during 2020 might have been mitigated by the implementation of remotely accessible consultations, so called telemedicine, a strategy that has been applied in other countries [ 31 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that healthcare systems should take actions to mitigate this shortcoming by allocating resources to primary care and geriatric clinics in order increase screening and diagnosis of new dementia cases. Decrease in registered dementia cases during 2020 might have been mitigated by the implementation of remotely accessible consultations, so called telemedicine, a strategy that has been applied in other countries [ 31 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…It seems that the changes in healthy lifestyle caused by the pandemic are varied in different countries (25), but many scholars still suggest that effective home physical activity and healthy eating strategies should be developed to help chronic patients maintain their health status (26,27). During this period, telephone coaching or counseling can be a suitable and effective method as well (28,29), and many studies have even confirmed the effectiveness of telephone coaching before the pandemic (30,31). Therefore, our study results indeed verify that behavioral coaching should help people with type 2 diabetes maintain a good lifestyle during the pandemic and even continue to improve their blood sugar control.…”
Section: Discussionmentioning
confidence: 99%
“…Singapore was one of the first countries in Southeast Asia to report confirmed COVID-19 cases and in less than a month from the first reported case, had the largest number of positive COVID-19 cases in the region. To cope with the rising cases and curb further spread of COVID-19 infections, resources were re-deployed to support acute essential services and non-critical outpatient and chronic care facilities were temporarily suspended (Lian et al, 2021). With the added public health advisories that those with diabetes and other chronic conditions were at increased the risk of hospitalization and death from COVID-19 (Caballero et al, 2020), the HRQoL of people with diabetes may have been adversely affected in this period as they grappled to adjust to new practices.…”
Section: Discussionmentioning
confidence: 99%